Influence of body segment inertia parameters on uncertainties in joint specific power during sprint cycling: A monte carlo simulation - Wheat, J.; Barrat, P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Joint-specific power analyses are important in the assessment of cycling biomechanics but they contain uncertainties due to errors in input parameters. The aim of the study was to investigate the effect of uncertainty in body segment parameters on joint-specific powers during maximal sprint cycling, using a Monte Carlo analysis. Joint powers were estimated using standard inverse dynamics techniques, with body segment parameters and uncertainty in these inputs defined using reference data. Monte Carlo simulations (10,000 iterations) were performed for pedal cycles at 120 rpm and 160 rpm. The analysis highlighted practically relevant uncertainties in peak hip joint power at racespecific pedalling rates caused by uncertainty in body segment parameters.